Myzocallis (Lineomyzocallis) walshii (Mon.), a new record far the Italian aphid fauna (Bollettino di zoologia agraria e bachicoltura, 2024)
The neartic aphid Myzocallis (Lineomyzocallis) walshii (Mon.) is recorded for the first time in Italy. It infests the red Oak (Quercus rubra), on which leaves several generations per year develop.
Keywords: Aphids; Myzocallis (Lineomyzacallis) walshii; Italy